2016
DOI: 10.1016/j.jbiomech.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a lateral pelvic cluster technical system in evaluating running kinematics

Abstract: Valid measurement of pelvic and hip angles during posterior load carriage gait task requires placement of pelvic markers which will not be occluded or physically displaced by the load. One solution is the use of pure lateral pelvic clusters to track the pelvis segment. However, the validity of this method has not been compared against pelvic marker systems recommended by the International Society of Biomechanics (ISB) during high impact tasks, such as running. The purpose of this study was to validate the late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Force data were used to detect initial contact and toe-off, with a 20 N vertical force threshold used. The marker placements were based on a previous study ( Liew et al, 2016b ). A seven-segment lower-limb biomechanical model was created in Visual 3D (C-motion, Germantown, MD, USA) ( Liew, Morris & Netto, 2016a ).…”
Section: Methodsmentioning
confidence: 99%
“…Force data were used to detect initial contact and toe-off, with a 20 N vertical force threshold used. The marker placements were based on a previous study ( Liew et al, 2016b ). A seven-segment lower-limb biomechanical model was created in Visual 3D (C-motion, Germantown, MD, USA) ( Liew, Morris & Netto, 2016a ).…”
Section: Methodsmentioning
confidence: 99%
“…Running kinematics were captured using an 18 camera motion analysis system (250 Hz, Vicon VX, Oxford Metrics, Inc.) and three in-ground force plates (2000 Hz, AMTI, Watertown, USA). Force data were used to define initial contact and toe-off using a threshold of 20 N. Retroreflective markers were placed bilaterally on the pelvis, thigh, shank and foot segments to create a seven segment biomechanical model [19]. Marker positions were placed by a single experimenter (A.M.), verified by an assistant (B.L), the latter having three years of motion capture experience.…”
Section: Biomechanical Testing Proceduresmentioning
confidence: 99%
“…This 10% frequency window was deemed appropriate given that a previous study reported a variation of up to 20 % for adults hopping at their preferred frequency (Beerse & Wu 2016) Manuscript to be reviewed off, with a 20 N vertical force threshold used. The marker placements were based on a previous study (Liew et al 2016b). A seven-segment lower-limb biomechanical model was created in Visual 3D (C-motion, Germantown, MD) (Liew et al 2016a).…”
Section: Three Dimension Motion Capture On Hopping (Combined Group Anmentioning
confidence: 99%